Resistência de cultivares de milho convencional e transgênico à Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) - Lopes, Gislane da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Diatraea saccharalis (Fabricius, 1794) is a lepidopteran that causes damage in several grasses such as sugar cane, maize, sorghum and rice. However there is little information regarding the use of resistance sources this borer in maize to Brazilian conditions. Thus this study aimed to determine the behavior of D. saccharalis in cultivars of transgenic and non-transgenic maize as feeding preference and antibiosis. The experiments were conducted between July 2011 to August 2013 with planting maize in a greenhouse in the area belonging to the Farm for Teaching, Research and Production and Laboratory of Plant Resistance to Insects, Department of Crop Protection, Faculty of Agricultural Sciences and Veterinary FCAV / UNESP, Jaboticabal. Conventional and transgenic cultivars were evaluated for feeding behavior in tests with multiple and non-choice tests on these time: 24, 48 and 72 hours. Soon after these results were evaluated the effects of plant age on food preference and antibiosis these cultivars. The data were transformed, if necessary, to maintain the curve of normality and then analysis of variance to the means. Results of feeding preference in conventional and transgenic cultivars tests separately indicated that caterpillars with 15 days old also consumed conventional maize cultivars in tests with multiple and non-choice. However, newly hatched caterpillars provided less percentage of damage in conventional farming 2B 587 in non-choice test and, transgenic maize cultivars SX8330 TL TG, DAS 2B707 HX, P 3646 HX, BG 7049 YG, DKB 789 YG and DKB 390 VTPRO provided the lowest ratings of damage symptoms to newly-hatched larvae of D. saccharalis. For tests involving transgenic and conventional cultivars simultaneously, was observed that SHS 7780 cultivar is susceptible and the cultivars DKB 390 VTPRO, DKB 789 YG and DAS 2B 707 showed resistance in the category feeding preference on D. saccharalis. On the evaluation of the age effect ...

A broca do colmo, Diatraea saccharalis (Fabricius, 1794), é um lepidóptero que ocasiona danos em diversas gramíneas como cana-de-açúcar, milho, sorgo e arroz. Todavia, poucas são as informações relacionadas ao uso de fontes de resistências dessa broca na cultura do milho para condições brasileiras. Assim, objetivou-se determinar o comportamento de D. saccharalis em cultivares de milho convencional e transgênico quanto a não preferência para alimentação e antibiose. Os experimentos foram conduzidos no período de agosto/2011 a julho/2013 com plantios de milho em casa de vegetação, localizada em área pertencente à Fazenda de Ensino, Pesquisa e Produção e no Laboratório de Resistência de Plantas a Insetos, do Departamento de Fitossanidade, da Faculdade de Ciências Agrárias e Veterinárias FCAV/UNESP, Campus Jaboticabal. Cultivares de milho convencionais e transgênicas foram avaliadas quanto ao comportamento de alimentação em testes com e sem chance de escolha, ambos com duração de 24, 48 e 72 horas. Em seguida, foram avaliados os efeitos da idade da planta na preferência alimentar de e a antibiose destas cultivares. Os dados foram transformados, quando necessário, para respeitar a curva de normalidade e, em seguida, foi realizada análise de variância das médias. Os resultados dos testes de preferência alimentar em cultivares de milho convencionais e transgênicas, separadamente, indicaram que lagartas com 15 dias de idade consomem igualmente as cultivares convencionais, em testes com e sem chance de escolha. No entanto, lagartas recém-eclodidas proporcionam menor dano na cultivar convencional 2B 587 em teste sem chance de escolha e as cultivares de milho transgênico SX8330 TL TG, DAS 2B707 HX, P 3646 HX, BG 7049 YG, DKB 789 YG e DKB 390 VTPRO proporcionam menores porcentagens de dano para lagartas recém-eclodidas de D. saccharalis. Para os testes envolvendo cultivares de milho convencionais e transgênicas ...
Keywords: Milho - Doenças e pragas; Plantas cultivares; Broca (Inseto); Plantas - Resistência aos insetos; Alimentos geneticamente modificados; Plants Insect resistance